Prevalence and predictors of pediculosis capitis among primary school children in Hulu Langat, Selangor - Mohd Tohit, Nor Faiza; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann (Malaysian Medical Association, 2017)
Introduction: Pediculosis capitis infestation is endemic in both developing and developed countries leading to various physical, economical and psychological consequences. Our main objective was to determine the prevalence and predictors of pediculosis capitis among primary school children in Hulu Langat District, Malaysia. Methods: An analytic cross-sectional study using cluster random sampling method was carried out in Hulu Langat District, Malaysia. Self-administered pretested questionnaires were used to collect the data. Hair and scalp examination was also carried out. Multivariate logistic regression was used to control for potential confounding and determine the predictors. Results: The overall mean age of the 1,336 respondents was 9.3 years. Majority were males (52.8%), Malays (79.5%) and 81.3% of the fathers had secondary or tertiary education as compared to 77.3% for the mothers. The overall prevalence of pediculosis capitis was 15.3%. The prevalence of pediculosis was significantly higher among females (28.4%) than males (3.7%, p=0.001). Multivariate logistic regression analysis showed that age 10 years or more (Odds Ratio (OR) = 2.34, 95% Confidence Interval (CI) = 1.673 to 3.272), female gender (OR = 10.26, 95% CI = 6.620 to 15.903), history of contact with an infested person (OR = 2.11, 95% CI = 1.506 to 2.960), Indian compared to Chinese (OR = 3.55, 95% CI = 1.282 to 9.860), Malay to Chinese (OR = 2.59, 95% CI =.994 to 6.774) were associated with pediculosis capitis. Conclusions: Prevalence of pediculosis capitis among children aged 7 - 12 years in Hulu Langat District was high. There is a need for screening and treatment of pediculosis capitis in primary schools.